2011
DOI: 10.1038/modpathol.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ErbB2 (Her2) in oesophageal adenocarcinomas: summary of a revised immunohistochemical evaluation system, bright field double in situ hybridisation and fluorescence in situ hybridisation

Abstract: Amplification and overexpression of ErbB2 (Her2) is a frequent event in oesophageal adenocarcinomas. Assessment of ErbB2 status is crucial for identifying patients who are likely to benefit from treatment with trastuzumab. In this study, we performed a comprehensive analysis of ErbB2 amplification and expression in 142 oesophageal adenocarcinomas by comparing the most commonly used methods for ErbB2 assessment: ErbB2 expression was determined by immunohistochemistry and was scored (0, 1 þ , 2 þ and 3 þ ) accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 31 publications
(63 reference statements)
8
25
1
Order By: Relevance
“…In hindsight, a tendency toward higher HER2 positivity rate in proximal gastric tumors which are now classified as esophageal tumors is thus apparent in these studies. On the other hand, distal esophageal primary tumors (without growth in the GEJ) in our study showed 31.5 % HER2 positivity, which is higher than the 15-29 % HER2 positivity rate found in studies on distal esophageal adenocarcinoma alone (Yoon et al 2012a, b;Phillips et al 2012;Reichelt et al 2007;Langer et al 2011;Hu et al 2011). This could be related to underlying Barrett's esophagus in the primary distal esophageal tumors included in our study, which was frequently reported (25 of 54 distal esophageal tumors).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In hindsight, a tendency toward higher HER2 positivity rate in proximal gastric tumors which are now classified as esophageal tumors is thus apparent in these studies. On the other hand, distal esophageal primary tumors (without growth in the GEJ) in our study showed 31.5 % HER2 positivity, which is higher than the 15-29 % HER2 positivity rate found in studies on distal esophageal adenocarcinoma alone (Yoon et al 2012a, b;Phillips et al 2012;Reichelt et al 2007;Langer et al 2011;Hu et al 2011). This could be related to underlying Barrett's esophagus in the primary distal esophageal tumors included in our study, which was frequently reported (25 of 54 distal esophageal tumors).…”
Section: Discussioncontrasting
confidence: 74%
“…Similar HER2 positivity rates are reported in esophageal adenocarcinoma, though less extensively studied (Yoon et al 2012a, b;Phillips et al 2012;Reichelt et al 2007;Langer et al 2011;Hu et al 2011).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…23,25 Some publications have suggested that HER2 overexpression is linked with poor prognosis in oesophageal cancer 26,27 while others have shown no relationship with prognosis. 28e30 Duhaylongsod et al 31 and Yoon et al 24 have stated that HER2 positive patients have better prognosis compared to HER2 negative patients, the latter study reporting that HER2 positivity was independently associated with improved overall survival with a HR ¼ 0.50 (95% CI: 0.33e0.78).…”
Section: Her2 Positive Survival Ratesmentioning
confidence: 99%
“…The most common receptor mutations seen in early stages of EAC are activating missense mutations and inframe deletions of the Epidermal Growth Factor Receptor (EGFR) [5]. On the other hand, HER2 and c-MYC amplifications tend to develop in later stages of the disease and are associated with poor prognosis [6,7]. Interestingly, recent data seem to suggest that HER2 and EGFR are frequently amplified synchronously and preferentially dimerize with one another [8].…”
Section: Introductionmentioning
confidence: 99%